2019
DOI: 10.1021/jacs.9b07779
|View full text |Cite
|
Sign up to set email alerts
|

Navigated Self-Assembly of a Pd2L4 Cage by Modulation of an Energy Landscape under Kinetic Control

Abstract: Kinetic control of molecular self-assembly remains difficult because of insufficient understanding of molecular selfassembly mechanism. Here we report the formation of a metastable [Pd2L4] 4+ cage structure composed of naphthalene-based ditopic ligands (L) and Pd(II) ions in very high yield (99%) under kinetic control by modulating the energy landscape. The guest anion trapped in the cage and the solvent with very weak coordination ability prefer the formation of suitable intermediates and prevent the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…We previously used density functional theory (DFT) formation energies to explain the thermodynamically preferred cage topologies in the dynamic imine-based selfassembly processes. [41,[57][58][59] Comparing the thermodynamic stabilities of potential cage products can be ag ood guide to selectivity,b ut the reaction outcome can also be affected by factors,s uch as reaction kinetics, [39,[60][61][62][63][64] solvent effects, [65][66][67][68] and the solubilities of the species involved in the equilibrium. [33,40,47] In parallel with the synthetic efforts,w eu sed computational techniques to predict the stability of the different homo-and heteroleptic structures originating from aldehydes B1-B2 and L1-L4.T he experimentally observed outcomes agreed with the relative gas-phase formation energies of the possible Tet 3 Di 6 products,s howing the predictive power of the simple model for the self-sorting behaviour of imine-based organic cages.…”
Section: Introductionmentioning
confidence: 99%
“…We previously used density functional theory (DFT) formation energies to explain the thermodynamically preferred cage topologies in the dynamic imine-based selfassembly processes. [41,[57][58][59] Comparing the thermodynamic stabilities of potential cage products can be ag ood guide to selectivity,b ut the reaction outcome can also be affected by factors,s uch as reaction kinetics, [39,[60][61][62][63][64] solvent effects, [65][66][67][68] and the solubilities of the species involved in the equilibrium. [33,40,47] In parallel with the synthetic efforts,w eu sed computational techniques to predict the stability of the different homo-and heteroleptic structures originating from aldehydes B1-B2 and L1-L4.T he experimentally observed outcomes agreed with the relative gas-phase formation energies of the possible Tet 3 Di 6 products,s howing the predictive power of the simple model for the self-sorting behaviour of imine-based organic cages.…”
Section: Introductionmentioning
confidence: 99%
“…NASAP for the (BF 4 − ) [Pd 2 4 4 ] 4+ cage assembly in the same reaction network model with five reaction types used for the (NO 3 − ) [Pd 2 3 4 ] 4+ cage (Figures 9a and 11c) showed that the rate constant of the final crosslinking ( k 5 ) is the smallest among the three intramolecular reactions ( k 3 , k 4 , and k 5 ), which is the same as seen in the [Pd 2 2 4 ] 4+ and the (NO 3 − ) [Pd 2 3 4 ] 4+ cages (Figure 12b) [16] . However, k 3 and k 4 for the (BF 4 − ) [Pd 2 4 4 ] 4+ cage are much smaller than those for the (NO 3 − ) [Pd 2 3 4 ] 4+ cage, indicating that more flexible ditopic ligand 3 is more advantageous for the cyclization probably due to the preferential formation of the distorted transition structure and intermediate of the cyclization, where one of the Pd(II) ions has to adopt five‐coordinate geometry [9]…”
Section: Qasap and Nasap For Pd(ii)‐linked Self‐assembliesmentioning
confidence: 60%
“…Recently, it was found that a metastable Pd 2 L 4 cage can be prepared under the QASAP condition [16] . The ditopic ligand 4 gave [Pd 2 4 4 ] 4+ cage only when a good template anion such as BF 4 − is present in the reaction mixture (Figure 12a).…”
Section: Qasap and Nasap For Pd(ii)‐linked Self‐assembliesmentioning
confidence: 99%
“…On the other hand, the donor strength of the ligand can be compensated by other factors ( e.g. anion effects), 23 as evidenced by the higher G ′ value of P1 when compared to what is found for P2 .…”
Section: Resultsmentioning
confidence: 98%